Basal activity of the hypothalamic-pituitary-adrenal axis in patients with the chronic fatigue syndrome (neurasthenia). - Young, A; Sharpe, M; Clements, A; Dowling, B; Hawton, K; Cowen, P (1998)
BACKGROUND: Impairments in both basal activity and activation of the hypothalamic-pituitary-adrenal axis (HPA) have been reported in chronic fatigue syndrome (CFS; neurasthenia). We sought to replicate these findings and examined basal activity of the HPA in a carefully selected sample of patients with CFS. METHODS: Basal activity of the HPA was assessed using salivary and urinary cortisol collection over a 24-hour period in 22 (12 male; 10 female) patients meeting criteria for CFS and appropriate controls. RESULTS: Salivary and urinary cortisol measures did not differ between CFS patients and controls. CONCLUSIONS: Basal activity of the HPA was not reduced in CFS patients. Reasons for the failure to replicate previous findings are discussed.